2018
DOI: 10.14419/ijet.v7i2.29.13325
|View full text |Cite
|
Sign up to set email alerts
|

The influence of E-WOM on purchase intentions in local culinary business sector

Abstract: With a large population and high consumer interest in local culinary, Indonesia becomes a potential market for small and medium-sized local culinary enterprises. However, most of local small and medium-sized enterprises (SMEs) in culinary sector face a wide range of challenges especially when it comes to huge promotion costs. Fortunately, the ever-increasing numbers of Internet users in Indonesia provides an opportunity for these SMEs to promote their products through Electronic Word of Mouth (E-WOM). E-WOM ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
13

Year Published

2018
2018
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 11 publications
0
31
0
13
Order By: Relevance
“…Brand image is important for companies if consumers have a favorable image as it can contribute to an increase in market share, and market success, thus allowing a firm to have a better position in the market (Sondoh et al, 2007). Several studies investigated the relationship between eWOM, purchase intention, and brand image were limited to specific countries and industries, so the previous scholars confirmed to explore this relationship in different context (countries, industries), also the previous studies indicated to study the research model with different potential moderator (Al Halbusi & Tehseen, 2018;Alam Hamdani & Abdul Fatah Maulani, 2018;Engel et al, 1969;Kazmi & Mehmood, 2016;Torlak et al, 2014). For this, few researchers have investigated eWOM communication, while none has looked to examine this research model in a Northern Cyprus context (developing countries).…”
Section: Introductionmentioning
confidence: 98%
“…Brand image is important for companies if consumers have a favorable image as it can contribute to an increase in market share, and market success, thus allowing a firm to have a better position in the market (Sondoh et al, 2007). Several studies investigated the relationship between eWOM, purchase intention, and brand image were limited to specific countries and industries, so the previous scholars confirmed to explore this relationship in different context (countries, industries), also the previous studies indicated to study the research model with different potential moderator (Al Halbusi & Tehseen, 2018;Alam Hamdani & Abdul Fatah Maulani, 2018;Engel et al, 1969;Kazmi & Mehmood, 2016;Torlak et al, 2014). For this, few researchers have investigated eWOM communication, while none has looked to examine this research model in a Northern Cyprus context (developing countries).…”
Section: Introductionmentioning
confidence: 98%
“…Storytelling is part of communication marketing. To build a brand from an online business, several marketing communication activities can be developed by marketers and non-marketers such as word-of-mouth (19). Brand storytelling is the ability to tell the brand aspects so as to form emotional relationships with stakeholders such as sales, public speakers, suppliers, distributors, and consumers who bring a message from a brand to others (5).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Senada dengan hal tersebut [2] menyebutkan bahwa UKM memiliki kotribusi besar dalam meningkatkan produk domestik bruto suatu bangsa. Beberapa penelitian menyebutkan bahawa Kinerja UKM ditentukan oleh teknologi diantaranya penelitian [3] dan [4]. Beberapa penelitian juga menjelaskan pentingnya peranan teknologi informasi pada UKM diantaranya [5] dan penelitian dari Oleh karena itu diperlukan perencanaan sistem informasi sebagai bagian dari implementasi teknologi yang dilakukan oleh UKM.…”
Section: Pendahuluanunclassified